Prevalence of radiological findings among cases of severe secondary hyperparathyroidism - Lacativa, Paulo Gustavo Sampaio; Franco, Felipe Malzac; Pimentel, José Raimundo; Patrício Filho, Pedro José de Mattos; Gonçalves, Manoel Domingos da Cruz; Farias, Maria Lucia Fleiuss (São Paulo Medical Journal, 2009)
CONTEXT AND OBJECTIVE: Patients with end stage renal disease (ESRD) and secondary hyperparathyroidism (HPT2) are prone to develop heterotopic calcifications and severe bone disease. Determination of the sites most commonly affected would decrease costs and patients’ exposure to X-ray radiation. The aim here was to determine which skeletal sites produce most radiographic findings, in order to evaluate hemodialysis patients with HPT2, and to describe the most prevalent radiographic findings. DESIGN AND SETTING: This study was cross-sectional, conducted in one center, the Hospital Universitário Clementino Fraga Filho (HUCFF), in Rio de Janeiro, Brazil. METHODS: Whole-body radiographs were obtained from 73 chronic hemodialysis patients with indications for parathyroidectomy due to severe HPT2. The regions studied were the skull, hands, wrists, clavicles, thoracic and lumbar column, long bones and pelvis. All the radiographs were analyzed by the same two radiologists, with great experience in bone disease interpretation. RESULTS: The most common abnormality was subperiosteal bone resorption, mostly at the phalanges and distal clavicles (94% of patients, each). “Rugger jersey spine” sign was found in 27%. Pathological fractures and deformities were seen in 27% and 33%, respectively. Calcifications were presented in 80%, mostly at the forearm fistula (42%), abdominal aorta and lower limb arteries (35% each). Brown tumors were present in 37% of the patients, mostly on the face and lower limbs (9% each). CONCLUSION: The greatest prevalence of bone findings were found on radiographs of the hands, wrists, lateral view of the thoracic and lumbar columns and femurs. The most prevalent findings were bone resorption and ectopic calcifications.